An investigation on the effect of real exchange rate movements on OECD bilateral exports - Antoine Berthou (European Central Bank (ECB), 2008)
The reaction of exports to real exchange rate movements can differ according to the nature of the destination country. We derive and estimate a gravity equation for 20 OECD exporting countries and 52 developed and developing importing countries. We test how trade costs dampen the effect of real exchange rate movements on bilateral exports, and show that the elasticity on the real exchange rate is reduced when (i) the destination country has a low quality of institutions, (ii) this country is more distant, and (iii) the efficiency of customs is low in both the importing and exporting countries. These results are highly consistent with the existence of an hysteresis effect of real exchange rate movements on trade, as suggested by Baldwin and Krugman (1989).
Keywords: F10; F32; D73; 330; Exchange Rate Movements; institutions; Trade; Kaufkraftparität; Handelseffekt; Transaktionskosten; Institutionelle Infrastruktur; OECD-Staaten; Industrieländer; Entwicklungsländer